1-(Biphenyl-4-ylcarbonyl)-3-(2-chloro-4-nitrophenyl)thiourea - Mohd Yusof , Mohd Sukeri; Mohd Yamin, Bohari; Ngah, Nurziana (International Union of Crystallography, 2012)
The benzene rings of the biphenyl group in the title compound, C20H14ClN3O3S, are nearly coplanar [maximum deviation = 0.20 (3) Å]. The mean plane of the biphenyl group forms a dihedral angle of 5.24 (7)° with the aromatic ring of the nitrochlorobenzene group. Intramolecular N-HCl, N-HO and C-HS hydrogen bonds stabilize the cis-trans conformation of the molecule. In the crystal, molecules are linked by C-HO and C-HS hydrogen bonds into mutually interwoven corrugated layers parallel to (10-2).